Advances in water resources research in the Upper Blue Nile basin and the way forward: A review - Tekleab, S. (2020)
This paper aims to bridge this gap by reviewing the advances in water resources research in the basin while highlighting research needs and future directions. We report that there have been several research projects that try to understand the biogeochemical processes by collecting information on runoff, groundwater recharge, sediment transport, and tracers. More recent research has been using advanced semi-physically/physically based distributed hydrological models using high-resolution temporal and spatial data for diverse applications. We identified several research gaps and provided recommendations to address them. While we have witnessed advances in water resources research in the basin, we also foresee opportunities for further advancement. Incorporating the research findings into policy and practice will significantly benefit the development and transformation agenda of the Ethiopian government.